Leave the past behind: women's reproductive history shows no association with blastocysts' euploidy and limited association with live birth rates after euploid embryo transfers. Issue 4 (20th February 2021) - Cimadomo, Danilo; Capalbo, Antonio; Dovere, Lisa; Tacconi, Luisa; Soscia, Daria; Giancani, Adriano; Scepi, Emiliano; Maggiulli, Roberta; Vaiarelli, Alberto; Rienzi, Laura; Ubaldi, Filippo Maria
Abstract: STUDY QUESTION: Is there an association between patients' reproductive history and the mean euploidy rates per biopsied blastocysts (m-ER) or the live birth rates (LBRs) per first single vitrified-warmed euploid blastocyst transfers? SUMMARY ANSWER: Patients' reproductive history (as annotated during counselling) showed no association with the m-ER, but a lower LBR was reported after euploid blastocyst transfer in women with a history of repeated implantation failure (RIF). WHAT IS KNOWN ALREADY: Several studies have investigated the association between the m-ER and (i) patients' basal characteristics, (ii) ovarian stimulation strategy and dosage, (iii) culture media and conditions, and (iv) embryo morphology and day of full blastocyst development. Conversely, the expected m-ER due to women's reproductive history (previous live births (LBs), miscarriages, failed IVF cycles and transfers, and lack of euploid blastocysts among prior cohorts of biopsied embryos) still needs investigations. Yet, this information is critical to counsel new patients about a first cycle with preimplantation genetic testing for aneuploidy (PGT-A), but even more so after former adverse outcomes to prevent treatment drop-out. STUDY DESIGN, SIZE, DURATION: This observational study included all patients undergoing a comprehensive chromosome testing (CCT)-based PGT-A cycle with at least one biopsied blastocyst in the period April 2013-December 2019 at a private IVF clinic (n = 2676 patients undergoing 2676 treatments and producing and 8151 blastocysts). m-ER were investigated according to women's reproductive history of LBs: no/≥1, miscarriages: no/1/>1; failed IVF cycles: no/1/2/>2, and implantation failures after previous transfers: no/1/2/>2. Among the 2676 patients included in this study, 440 (16%) had already undergone PGT-A before the study period; the data from these patients were further clustered according to the presence or absence of euploid embryo(s) in their previous cohort of biopsied blastocysts. The clinical outcomes per first single vitrified-warmed euploid blastocyst transfers (n =1580) were investigated according to the number of patients' previous miscarriages and implantation failures. PARTICIPANTS/MATERIALS, SETTING, METHODS: The procedures involved in this study included ICSI, blastocyst culture, trophectoderm biopsy without hatching in Day 3, CCT-based PGT-A without reporting segmental and/or putative mitotic (or mosaic) aneuploidies and single vitrified-warmed euploid blastocyst transfer. For statistical analysis, Mann–Whitney U or Kruskal–Wallis tests, as well as linear regressions and generalised linear models among ranges of maternal age at oocyte retrieval were performed to identify significant differences for continuous variables. Fisher's exact tests and multivariate logistic regression analyses were instead used for categorical variables. MAIN RESULTS AND THE ROLE OF CHANCE: Maternal age at oocyte retrieval was the only variable significantly associated with the m-ER. We defined five clusters (<35 years: 66 ± 31%; 35–37 years: 58 ± 33%; 38–40 years: 43 ± 35%; 40–42 years: 28 ± 34%; and >42 years: 17 ± 31%) and all analyses were conducted among them. The m-ER did not show any association with the number of previous LBs, miscarriages, failed IVF cycles or implantation failures. Among patients who had already undergone PGT-A before the study period, the m-ER did not associate with the absence (or presence) of euploid blastocysts in their former cohort of biopsied embryos. Regarding clinical outcomes of the first single vitrified-warmed euploid blastocyst transfer, the implantation rate was 51%, the miscarriage rate was 14% and the LBR was 44%. This LBR was independent of the number of previous miscarriages, but showed a decreasing trend depending on the number of previous implantation failures, reaching statistical significance when comparing patients with >2 failures and patients with no prior failure (36% versus 47%, P < 0.01; multivariate-OR adjusted for embryo quality and day of full blastocyst development: 0.64, 95% CI 0.48–0.86, P < 0.01). No such differences were shown for previous miscarriage rates. LIMITATIONS, REASONS FOR CAUTION: The sample size for treatments following a former completed PGT-A cycle should be larger in future studies. The data should be confirmed from a multicentre perspective. The analysis should be performed also in non-PGT cycles and/or including patients who did not produce blastocysts, in order to investigate a putative association between women's reproductive history with outcomes other than euploidy and LBRs. WIDER IMPLICATIONS OF THE FINDINGS: These data are critical to counsel infertile couples before, during and after a PGT-A cycle, especially to prevent treatment discontinuation due to previous adverse reproductive events. Beyond the 'maternal age effect', the causes of idiopathic recurrent pregnancy loss (RPL) and RIF are likely to be endometrial receptivity and selectivity issues; transferring euploid blastocysts might reduce the risk of a further miscarriage, but more information beyond euploidy are required to improve the prognosis in case of RIF. STUDY FUNDING/COMPETING INTEREST(S): No funding was received and there are no competing interests. TRIAL REGISTRATION NUMBER: N/A.